Outcome of Homoeopathic Intervention in Psychiatric Inpatients Treated in Rural Homoeopathic Hospital, Palghar, Maharashtra, India, 2014–2018: A Retrospective Analysis - Nikumbh, Sunita; Kukde, Abhishek; Patel, Manoj; Parekh, Bhavik; Nigwekar, Anoop; Mittal, Renu; Dhawale, Kumar (Homœopathic Links, 2022)
Background Rural homoeopathic hospital has been serving the community in and around Palghar for the past 20 years. Through a Central Government Scheme of Centre of Excellence, it received funds for setting up an inpatient psychiatric unit in 2012 whereby it could serve the wider community by admitting the patients with mental illness in a secure ward. This is the second of two papers on the experience of homoeopathic treatment of psychiatric inpatients and details of the outcome of homoeopathic treatment to patients admitted between 2014 and 2018.Objective Efforts have been made to explore the outcomes of homoeopathic intervention, singly or as adjuvant treatment, for a variety of clinical conditions and to determine the commonly indicated remedies that were found useful.Methodology A standard operating procedure enabled symptom analysis and evaluation; it also enabled to erect the homoeopathic totality and institute treatment along with conducting the follow-up. Retrospective analysis using Outcome Related to Impact on Daily Living scale helped to establish the results of homoeopathic intervention.Results An excellent response to homoeopathic intervention was obtained for several clinical conditions like alcohol withdrawal (76.3%), conversion disorder (82.17%), suicide attempt (85.13%), anxiety disorders (84.19%), depressive disorders (75%) and somatoform (85.17%). The rate of improvement in schizophrenia (60%) and epilepsy (22.6%) was lower. The commonly indicated homoeopathic remedies for each clinical condition were identified. This information would help practitioners to acquire knowledge of a pool of remedies from which they could readily determine the similimum.Conclusion Homoeopathic treatment, either alone or as an adjuvant, is useful in the management of psychiatric inpatients for several clinical conditions. Remedies found useful in different clinical conditions need to be studied in greater depth to identify their leading indications.
Keywords: common homoeopathic remedies; homoeopathy treatment; ORIDL scale; psychiatry inpatients